2016
DOI: 10.1007/s40121-016-0134-x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Treating All Stages of Chronic Hepatitis C: A Comprehensive Review of Clinical and Economic Evidence

Abstract: IntroductionThe goal of chronic hepatitis C (CHC) treatment is to achieve a sustained virologic response (SVR). The new generation of direct-acting antivirals (DAAs) offers 90–100% SVR rates. However, access to these treatments is generally limited to patients with advanced liver disease. The aim of this review is to provide an overview of the clinical and economic benefits of achieving SVR and to better understand the full value of CHC treatment in all stages of liver disease.MethodsA comprehensive literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 99 publications
1
34
1
Order By: Relevance
“…Although progressive hepatic fibrosis is responsible for most HCV morbidity and mortality,19 studies with a 5-year to 12-year follow-up have suggested that non-cirrhotic patients in particular benefit from a significant decrease in mortality on achieving SVR 20. In this meta-analysis, data were extracted from 48 predominantly prospective and retrospective cohort studies that examined the effect of achieving SVR on a variety of extrahepatic outcomes in HCV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although progressive hepatic fibrosis is responsible for most HCV morbidity and mortality,19 studies with a 5-year to 12-year follow-up have suggested that non-cirrhotic patients in particular benefit from a significant decrease in mortality on achieving SVR 20. In this meta-analysis, data were extracted from 48 predominantly prospective and retrospective cohort studies that examined the effect of achieving SVR on a variety of extrahepatic outcomes in HCV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with decompensated liver disease, SVR can lead to resolution of ascites, a reduction in portal hypertension, and sustained improvement in synthetic liver function. Older adults are less likely to be candidates for liver transplantation, so the improvement in liver function associated with viral eradication can confer a significant mortality benefit for individuals with advanced liver disease …”
Section: Discussionmentioning
confidence: 99%
“…DAAs have shown excellent safety and tolerability in HCV patients of all genotypes, with sustained virologic response (SVR) rates in excess of 95% in most subpopulations and significant improvements on patient‐reported outcomes . There are a large number of studies that document the significant morbidity and mortality benefit of achieving SVR in HCV patients at all stages of fibrosis . Thus, early treatment with DAAs can prevent a substantial portion of direct medical costs related to downstream hepatic HCV complications .…”
Section: Introductionmentioning
confidence: 99%